2009
DOI: 10.2754/avb200978010093
|View full text |Cite
|
Sign up to set email alerts
|

Stress in Broiler Chickens Due to Acute Noise Exposure

Abstract: Stress effects from acute noise exposure were monitored in a group of ROSS 308 broiler chickens (n = 80), aged 42 days. The experiment simulated slaughterhouse sounds to which the broilers were exposed for 10 min in the test enclosure. Effects of acute noise exposure at two different levels (80 dB and 100 dB) were evaluated on the basis of examinations of selected biochemical plasma indicators and tonic immobility tests. Noise stimuli of both 80 dB and 100 dB intensities for 10 min induced a significant elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
2
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 20 publications
(26 reference statements)
0
40
2
5
Order By: Relevance
“…This type of response may indicate the ability of broilers to adapt to an increased level of noise at 100 dB intensity after the first 12 min of exposure. In contrast to our experiment, Chloupek et al (2009) did not find any changes in plasma triglycerides and glucose concentrations in broilers exposed to noise at 80 and 100 dB for 10 min. These authors also described a significant increase in the cholesterol level in broilers following 10 min of noise exposure at 100 dB, which is in contradiction with our findings, in that cholesterol concentrations showed various temporal patterns with no significant difference between 100 dB and control broilers for the whole period monitored in our experiment.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…This type of response may indicate the ability of broilers to adapt to an increased level of noise at 100 dB intensity after the first 12 min of exposure. In contrast to our experiment, Chloupek et al (2009) did not find any changes in plasma triglycerides and glucose concentrations in broilers exposed to noise at 80 and 100 dB for 10 min. These authors also described a significant increase in the cholesterol level in broilers following 10 min of noise exposure at 100 dB, which is in contradiction with our findings, in that cholesterol concentrations showed various temporal patterns with no significant difference between 100 dB and control broilers for the whole period monitored in our experiment.…”
Section: Resultscontrasting
confidence: 99%
“…The corticosterone concentration reached its highest values from Time 10 min to 14 min in 100 dB broilers in our experiment, then decreased again to the prestress concentration at 28 min. Chloupek et al (2009) also described a significant increase in the corticosterone level after 10 min of noise exposure at 80 dB and 100 dB in broilers. McFarlane and Curtis (1989), who reported that plasma corticosterone was unaffected by continuous noise at a level of 95 dB on trial Day 7 in broiler chicks, support our findings regarding a following decrease in corticosterone levels after 14 min of exposure to the elevated noise in our experiment.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Chloupek ve ark. 16 yaptıkları benzer bir çalışmada etlik piliçleri 80 ve 100 dB şiddetinde akut gürültüye maruz bırakmışlar ve gruplardaki kortikosteron düzeylerini sırasıyla 3200 ve 4740 pg/ml olarak tespit etmişlerdir. Bedanova ve ark.…”
Section: Tartişma Ve Sonuçunclassified
“…Çalışmada bulunan kortikosteron düzeylerinin hem Chloupek ve ark. 16 hem de Bedanova ve ark. 10 'nın değerlerinden daha düşük olduğu görülmektedir.…”
Section: Tartişma Ve Sonuçunclassified